2012
DOI: 10.4103/0259-1162.103378
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic role of tranexamic acid to reduce blood loss during radical surgery: A prospective study

Abstract: Background:The radical surgical procedures are associated with perioperative blood loss. This study was aimed to evaluate the clinical efficacy and safety of tranexamic acid in reducing perioperative blood loss in patients undergoing radical surgery.Materials and Methods:Sixty ASA class I and II adult consented female patients, scheduled for elective radical surgery and met the inclusion criterion, were blindly randomized into two groups to receive either intravenous 1 g tranexamic acid 20 min before skin inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…Gupta et al . [ 28 ] in their study on modified radical mastectomy and Wertheim's operation found that 1 g IV TA administered prophylactically 20 min before skin incision reduced the blood loss and transfusion requirement without any side effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al . [ 28 ] in their study on modified radical mastectomy and Wertheim's operation found that 1 g IV TA administered prophylactically 20 min before skin incision reduced the blood loss and transfusion requirement without any side effect.…”
Section: Discussionmentioning
confidence: 99%
“…A work by Smit proved that perioperative administration of TXA was associated with reduction in blood loss in patients who had total knee arthroplasty without any history of haematological disorders . It was further supported by Gupta's work which showed that IV administration of TXA could significantly reduce blood loss in radical surgeries . CRASH‐2 clinical trial proved that early administration of TXA can significantly reduce mortality in trauma patients although it has no effect on transfusion requirements .…”
Section: Discussionmentioning
confidence: 97%
“…Different studies have demonstrated that the use of tranexamic acid does not increase the incidence of thromboembolic events [ 11 , 15 ]. In this study, it was not possible to evaluate this outcome because data on this variable were found in only one publication and there were no significant differences.…”
Section: Discussionmentioning
confidence: 99%